Isoform-specific vs. pan-histone deacetylase inhibition as approaches for countering glioblastoma: an in vitro study - Joshi, Ameya; Ratnapradipa, Natasha; Hughes, Jayce; Moore, Erik; Ekpenyong, Andrew; Shukla, Surabhi (Frontiers in Oncology, 2025)
IntroductionGlioblastoma (GBM) is a grade 4 brain tumor that originates in astrocytes. GBM has a high death rate and a very low median patient survival rate of 14–16 months, even with well-established treatment regimens. The majority of preclinical models assess the effectiveness of molecular leads on two-dimensional (2D) cell cultures, which may provide insight into toxicity against particular genotypes of GBM but do not provide insight into the mechanism of action of the therapeutic drug. Three-dimensional (3D) cultures present an attractive alternative due to their ability to closely model in vivo tumor-like conditions.MethodsIn the present study, we used a rotary cell culture technique to culture 3D cancer spheroids of the T98G cell line. Initially, we estimated the relative potency of histone deacetylase (HDAC) inhibitors, which are molecular leads currently in clinical trials as epigenetic therapy for GBM, on 2D and 3D cultures of T98G. We characterized the effect of the 3D half-maximal inhibitory concentrations (IC50) on spheroids using a live–dead assay to figure out which inhibitors inhibited cell viability in 3D the most. Finally, we checked the effects of the non-specific and specific inhibitors on tumor migration dynamics using an electric cell impedance sensing (ECIS) device with the help of two parameters—rate of migration (ROM) and late resistance (LR).Results and discussionOur results show that the specific HDAC-6 inhibitor Tubacin had a more potent anti-proliferative effect in both the cytotoxicity and live–dead assays. The non-specific inhibitor Vorinostat surprisingly promoted migration in the cells at its 2D IC50 value treatment, and none of the inhibitors was able to significantly decrease late resistance compared to untreated controls, indicating the need for the development of more potent HDAC inhibitors for monotherapy for GBM.